How alcohol use problem severity affects the outcome of brief intervention delivered in-person versus through computer-generated feedback letters. (1st February 2018) - Baumann, Sophie; Gaertner, Beate; Haberecht, Katja; Bischof, Gallus; John, Ulrich; Freyer-Adam, Jennis
Highlights: Participants with different Alcohol Use Disorder Identification Test (AUDIT) score benefitted differently from intervention. Computer-generated feedback reduced alcohol use in persons with low AUDIT scores. Two third of the proactively recruited participants scored 8 or less on the AUDIT. Patients scoring high on the AUDIT may require more intensive care. The AUDIT provides a useful guidance for alcohol intervention at general hospitals. Abstract: Objective: The aim was to test if people with different alcohol use problem severity benefitted differentially from brief alcohol interventions delivered in-person versus through computer-generated feedback letters. Methods: Nine hundred sixty-one 18–64 year old general hospital inpatients with at-risk alcohol use (mean age = 40.9 years [standard deviation = 14.1], 75% men) were randomized to a) in-person counseling, b) computer-generated individualized feedback letters, or c) assessment only. Both interventions were delivered on the ward and 1 and 3 months later. Outcome was the change in the self-reported alcohol use per day at 6-, 12-, 18-, and 24-month follow-up. The Alcohol Use Disorder Identification Test (AUDIT) score was tested as a moderator of the effect of in-person counseling and computer-generated feedback letters, with higher AUDIT scores indicating more severe alcohol problems. Results: Compared to assessment only, computer-generated feedback letters more strongly reduced alcohol use over 24 months among persons with AUDIT scores of about 8 and lower ( p s < 0.05). In-person counseling tended to be superior over assessment only among persons scoring high on the AUDIT, but differences were not statistically significant. Six-, 12-, and 18-month differences between in-person counseling and computer-generated feedback letters were significant ( p s < 0.05) for persons with AUDIT scores below 7.1–7.7. The differences between both interventions attenuated at 24-month follow-up. Conclusions: Computer-based intervention delivery may be superior over in-person delivery for people with low levels of alcohol use problem severity, whereas those with more severe alcohol problems may require more intensive care.